The Study of Toshiba Singapore - Computer Systems Division (CSD) Information System - Tan, Sze Hui (2007)
With increasing competitive economy due to worldwide globalization and new technologies advances, firms today have to develop continuously, improve existing as well as to create new resources and capabilities in response to rapidly changing market conditions to sustain competitiveness.